Deficiency of FAM3D (Family With Sequence Similarity 3, Member D), A Novel Chemokine, Attenuates Neutrophil Recruitment and Ameliorates Abdominal Aortic Aneurysm Development. Issue 7 (July 2018) - He, Li; Fu, Yi; Deng, Jingna; Shen, Yicong; Wang, Yingbao; Yu, Fang; Xie, Nan; Chen, Zhongjiang; Hong, Tianpei; Peng, Xinjian; Li, Qingqing; Zhou, Jing; et al.
Abstract : Objective—: Chemokine-mediated neutrophil recruitment contributes to the pathogenesis of abdominal aortic aneurysm (AAA) and may serve as a promising therapeutic target. FAM3D (family with sequence similarity 3, member D) is a recently identified novel chemokine. Here, we aimed to explore the role of FAM3D in neutrophil recruitment and AAA development. Approach and Results—: FAM3D was markedly upregulated in human AAA tissues, as well as both elastase- and CaPO4 -induced mouse aneurysmal aortas. FAM3D deficiency significantly attenuated the development of AAA in both mouse models. Flow cytometry analysis indicated that FAM3D −/− mice exhibited decreased neutrophil infiltration in the aorta during the early stage of AAA formation compared with their wild-type littermates. Moreover, application of FAM3D-neutralizing antibody 6D7 through intraperitoneal injection markedly ameliorated elastase-induced AAA formation and neutrophil infiltration. Further, in vitro coculture experiments with FAM3D-neutralizing antibody 6D7 and in vivo intravital microscopic analysis indicated that endothelial cell–derived FAM3D induced neutrophil recruitment. Mechanistically, FAM3D upregulated and activated Mac-1 (macrophage-1 antigen) in neutrophils, whereas inhibition of FPR1 (formyl peptide receptor 1) or FPR2 significantly blocked FAM3D-induced Mac-1 activation, indicating that the effect of FAM3D was dependent on both FPRs. Moreover, specific inhibitors of FPR signaling related to Gi protein or β-arrestin inhibited FAM3D-activated Mac-1 in vitro, whereas FAM3D deficiency decreased the activation of both FPR-Gi protein and β-arrestin signaling in neutrophils in vivo. Conclusions—: FAM3D, as a dual agonist of FPR1 and FPR2, induced Mac-1-mediated neutrophil recruitment and aggravated AAA development through FPR-related Gi protein and β-arrestin signaling. Abstract : Supplemental Digital Content is available in the text.